Solvent-free oxidation of benzyl alcohols catalysed by a tetrazole-saccharinate Zn(II) complex under microwave radiation: the role of the ligand and the reaction mechanism - Frija, Luis M. T. (2021)
Herein we present an efficient methodology for the microwave-assisted peroxidative oxidation of benzyl alcohols to the corresponding aldehydes by using a novel and stable tetrazole-saccharinate zinc(II) catalyst, along with some insights into the reaction mechanism. This methodology is distinguished by the use of easily available and cheap reagents on the genesis of the zinc catalyst, mild reaction conditions, very short reaction periods (5-20 min) and no need to add an organic solvent. Furthermore, the use of TBHP (70%. aq.) as oxidizing agent turn this protocol a convenient one for benzyl alcohol oxidation in yields up to 98%. (C) 2020 Elsevier B.V. All rights reserved.